Reconstrucción de experiencias de niños, niñas y adolescentes en cuidados primarios pediátricos en clave de autonomía (2021)
The objective of this research was to recognize the experiences based on the secondary needs related to the development of the autonomy of children and adolescents with hospital stays in the area of primary pediatric care of the Departmental Hospital of Villavicencio (HDV). It is developed through a qualitative methodology with interviews at a depth of a group of 60 children and adolescents between 5 and 14 years, which were coded through analysis matrices. The importance of autonomy is considered as a primary need to satisfy hospital contexts, terms of socialization, play and free time. Likewise, the need to consider the decision-making and information processes of both paediatric users and their families, to guarantee adherence to treatment and resilience processes and adaptation to these contexts.